The Handbook Of Discourse Analysis - Schiffrin, Deborah , Tannen, Deborah and Hamilton, Heidi E. (USA: Blackwell Publishing, 2003)
This handbook makes significant contributions to current research and serves as a comprehensive and authoritative guide to the central issues in contemporary discourse analysis.
Includes Bibliographical References and Index.
Keywords: Discourse analysis-Handbooks